Evaluation of Behavior of a Deep Excavation by Three-dimensional Numerical Modeling - Tabaroei, Abdollah; Sarfarazi, Vahab; Pouraminian, Majid; Mohammadzadeh S., Danial (Periodica Polytechnica Civil Engineering, 2022)
To stabilize the urban deep excavations, soil anchoring is one of the methods that are very common for geotechnical engineers. Most of the previous studies have used a simplified the complex interaction and often they have overlooked the effects of three-dimensional (3D) modeling. In this study, the results of 11 3D finite element (FE) analysis of a deep excavation which supported with tie-back wall are presents. For this purpose, Firstly, the Texas A&M excavation which supported by two rows of ground anchors, soldier pile and wood lagging was modeled and secondly the results obtained from 3D numerical modeling have been compared with those obtained from measured data and the results of previous study. Then, the effect of ground anchors arrangement on the excavation behavior including horizontal displacement of the wall (δh) and surface settlement (δv) and their maximum values have been investigated. The results showed that a change in the value of SV1 does not have a significant effect on the value of maximum horizontal displacement of the wall (δhm). The value of SV1 has a significant effect on the value of (δv and by increasing its value from5 m to 2.5 m; the heave created at edge of the wall disappears and at d≥–1 m surface settlement created. When De=16 m, a variation in ground anchors arrangement significantly affected the values of maximum surface settlement (δvm) as compared to δhm. The results presented in this study can be helpful for designers without experience and information of previous designs.